IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN KSPPS BMT BAHTERA: UIN KH. Abdurrahman Wahid Pekalongan - SHOVIANA, EVI; MINNATAKA, ARINI (PT. Media Edutama Nusantara, 2024)
This research discusses the implementation of Corporate Social Responsibility (CSR) at the BMT Bahtera Sharia Savings and Loans and Financing Cooperative (KSPPS). CSR is an important aspect in building harmonious relationships between companies and the community and surrounding environment. This research aims to understand how KSPPS BMT Bahtera implements CSR based on the Triple Bottom Line (TBL) concept, which includes the aspects of Profit, People and Planet. The research method used is qualitative, with data collection techniques through interviews with related parties, including members, employees and the surrounding community. The results of the research show that KSPPS BMT Bahtera implements CSR through several programs, including: economic programs (entrepreneurial development, janitorial community, and oyster mushroom cultivation), educational and da'wah programs (scholarships and tahfidz houses), health programs (care cars, service health, and blood donation), as well as social and disaster programs (compensation for orphans and assistance to disaster victims). BMT Bahtera formed the Baitul Maal institution as a means to manage CSR funds sourced from customers, employees and donors. The implementation of this CSR has been proven to provide significant benefits in both economic, social and environmental aspects for the communities around BMT Bahtera's operations. This research concludes that a Triple Bottom Line-based CSR approach can help create a balance between economic, social and environmental aspects, while supporting the long-term sustainability of BMT Bahtera's business.